2015
DOI: 10.5154/r.rchscfa.2014.07.031
|View full text |Cite
|
Sign up to set email alerts
|

Restauración ecológica post-incendio de un bosque mixto de Pinus-Quercus del noreste de México

Abstract: La presente investigación se desarrolló en un bosque de Pinus-Quercus en el Parque Ecológico Chipinque (noreste de México), el cual fue afectado por un incendio forestal y sometido a tratamiento de restauración ecológica. Los objetivos fueron evaluar el establecimiento artificial de Pinus pseudostrobus (Lindl.) y analizar el efecto de las barreras de retención de suelo después de 10 años de su instalación. Para ello se estableció un área de estudio con tratamiento de restauración ecológica y otra área sin trat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 25 publications
(36 reference statements)
0
1
1
Order By: Relevance
“…In many countries, reforestation by planting after site preparation is considered as the most successful reforestation technique and is often preferred over seeding (Espelta et al, 2003;Pausas et al, 2004;Ginzburg and Steinberger, 2012;Alanís-Rodríguez et al, 2015). This could not be confirmed by our study.…”
Section: Active Restorationcontrasting
confidence: 73%
“…In many countries, reforestation by planting after site preparation is considered as the most successful reforestation technique and is often preferred over seeding (Espelta et al, 2003;Pausas et al, 2004;Ginzburg and Steinberger, 2012;Alanís-Rodríguez et al, 2015). This could not be confirmed by our study.…”
Section: Active Restorationcontrasting
confidence: 73%
“…In another study, Radulovich [19] observed that after three years, SB increased soil retention once vegetation was established. Alanís-Rodríguez et al [20] found that after 10 years soil depth increased by up to 25%. Similarly, SB have been reported to decrease soil loss by up to 68% annually with a sediment accumulation of 59-ton ha −1 [21].…”
Section: Introductionmentioning
confidence: 99%